Snacks and ice cream as complementary dog feed: perspectives, trends, ingredients - Freiberga, Anete; Ilgaza, Aija; Strausa, Evita; Ciprovica, Inga; Zagorska, Jelena (Frontiers in Animal Science, 2025)
This review explores the dog snack market, emphasizing pet ice cream as a growing sector with potential for further development. It examines current trends and production challenges in creating dog-friendly snacks that are safe and palatable. The review was conducted using a semi-systematic literature analysis from 2000 to 2024, evaluating over 65 full-text articles and other sources from major databases. Key topics covered include the types, ingredients, and functionality of dog snacks. Dog snacks are categorized by function and nutritional benefits, with a range of ingredients. The review identifies a gap in cooling dog snacks, highlighting ice cream as a promising product, noting that ice cream for dogs is different from classical ice cream and involves ingredients due to dogs’ dietary needs. Functional ingredients like probiotics and prebiotics are discussed for their health benefits. The review underscores the importance of further research to meet pet owners’ demands for safe, innovative, and functional dog snacks, particularly with respect to cooling treats and specialized dietary formulations. This research aligns with the growing trend toward pet wellness, reflecting owners’ increasing interest in snacks that are not only enjoyable but also contribute to overall pet health.